Power of Control Chart for the Ratio of Two Poisson Distributions Under Misclassification Error - Khurshid, Anwer; Chakraborty, Ashit B (Yugoslav Journal of Operations Research; Vol 30 No 2 (2020), 2020)
The effects of misclassification on the performance of control charts have been reconnoitered by several authors. Measurement error variability has uncertainty which can be from several sources. In this paper, we study the effect of the two sources of variability on the power characteristics of control chart and obtain the values of average run length () for the ratio of two Poisson distributions as studied by Sahai and Khurshid [30]. Expression of the power of control chart for variable sample size under standardized normal variate for ratio of two Poisson distributions is also derived.   Keywords : Measurement error, ratio of Poisson distribution, Average Run Length (), power.